A direct coupling numerical method for solving three-dimensional interaction problems of wave and floating structures. (June 2015) - Kao, Jeng-Hong; Lee, Jaw-Fang; Yu-Chun, Cheng
Abstract: In this article, a direct numerical method is developed to solve three-dimensional interaction problems of wave and floating structures. In the problem formulation, the diffracted wave and radiated wave by the structure are represented as one induced wave potential. The wave field is simulated using a boundary element method, and the structure motions are of six degrees of freedom. In the solution procedure, the structural motions are expressed in terms of wave potentials, which are then substituted into the wave model. The created linear algebraic system is then calculated. The present numerical model is used to simulate a floating rectangular cuboid deployed in a wave channel, and the results are compared with a theory to confirm the accuracy. The present numerical model is further used to calculate a floating structure deployed in an open sea to show the capability of the three-dimensional computation.